Speckle Tracking Echocardiography for the Assessment of the Athlete’s Heart: Is It Ready for Daily Practice? - Forsythe, Lynsey (Curr Treat Options Cardiovasc Med, 2018)
PURPOSE OF REVIEW: To describe the use of speckle tracking echocardiography (STE) in the biventricular assessment of athletes’ heart (AH). Can STE aid differential diagnosis during pre-participation cardiac screening (PCS) of athletes? RECENT FINDINGS: Data from recent patient, population and athlete studies suggest potential discriminatory value of STE, alongside standard echocardiographic measurements, in the early detection of clinically relevant systolic dysfunction. STE can also contribute to subsequent prognosis and risk stratification. SUMMARY: Despite some heterogeneity in STE data in athletes, left ventricular global longitudinal strain (GLS) and right ventricular longitudinal strain (RV ɛ) indices can add to differential diagnostic protocols in PCS. STE should be used in addition to standard echocardiographic tools and be conducted by an experienced operator with significant knowledge of the AH. Other indices, including left ventricular circumferential strain and twist, may provide insight, but further research in clinical and athletic populations is warranted. This review also raises the potential role for STE measures performed during exercise as well as in serial follow-up as a method to improve diagnostic yield.